Big data and the Facebook scandal: Issues and responses - Fuller, Michael E. (Theology, 2019)
The recent scandal over the appropriation of users' data from the Facebook platform serves to surface wider concerns about 'big data', relating inter alia to the ways in which personal data are obtained, stored and used for commercial purposes. This article outlines some of the issues involved, and sketches some of the ways in which theologically inspired reflection and action might begin to address those issues.